Proceedings of the 2012 IEEE Global Engineering Education Conference (EDUCON) 2012
DOI: 10.1109/educon.2012.6201020
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of success in engineering study

Abstract: The New Zealand Government is moving towards restricting access to tertiary education and implementing a managed entry scheme. It is therefore important to be able to predict whether a student has a reasonable likelihood of succeeding in tertiary engineering study.New Zealand secondary schools mostly operate on the National Certificate of Educational Achievement (NCEA) model whereby subjects are assessed on the basis of discrete individual modules. The paper compares the NCEA results to first year grades in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Previous work by the authors [1] helped us to identify the mathematics and physics preparation deficit. This was discussed in some depth in previous sections.…”
Section: Retention Solutionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work by the authors [1] helped us to identify the mathematics and physics preparation deficit. This was discussed in some depth in previous sections.…”
Section: Retention Solutionsmentioning
confidence: 98%
“…Most New Zealand secondary schools operate the National Certificate of Education Achievement (NCEA) form of assessment. Problems with this assessment are detailed elsewhere [1] but will be briefly summarized in Section II.…”
mentioning
confidence: 99%
“…For the first intake of students in 2007, we had no doubt whatsoever that our degree was of a very high academic quality and that the graduates we would produce would be equipped both to attain ready employment in industry and also to progress to postgraduate study at almost any institution. We were unable to fully define the entry criteria for enrolment into the degree due to a combination of university policy and a problematic form of High School assessment that made an evaluation of a student's academic ability problematic (refer [2] for a discussion of this). Therefore, in order to ensure the quality of our graduates, we mandated that all students pass the required suite of first year courses with the above average grade of B (65%), noting that in the New Zealand academic system a nominal pass grade is a C (50%).…”
Section: The Degree Constructionmentioning
confidence: 99%
“…Whilst a moderate predictor could be formed for the ECEN students based on physics and calculus, no such predictor could be formed for the NWEN and SWEN students [2]. It was apparent however, that despite the difficulties in directly assessing academic quality on the basis of High School grades, it was clear that student study habits and skills were extremely poor, due in a large part to NCEA grading, module selection, and ability to re-sit assessments that had previously been failed.…”
Section: Our Investigationmentioning
confidence: 99%
“…This comparison of student first year tertiary grades and their final year secondary school performance indicated that there are major gaps in levels of knowledge and learning abilities amongst most students. Crucially, the data revealed that prediction of success in first year tertiary engineering based on secondary school results was only possible for the ECEN major and even then was problematic [2]. This is significant since the New Zealand Government began in 2012 to link 5 percent of government funding for tertiary providers to student performance and dropout rates [3].…”
Section: Introductionmentioning
confidence: 99%